Measuring Gen Z's customer delight towards online food delivery services in Tacloban City using service quality indicators implications for service support - Estrera, April Joy G.; Gianan, Mae Kyle B.; Juego, Alynnah Kaye A.; Pedrera, Jackie R.
The growth of Online Food Delivery (OFD) services in the Philippines is rapidly increasing. There is a notable trend in providers and consumers adopting OFD services. Generation Z is associated with technology, and individuals from this Generation express a preference for using online applications for their orders. It is considered as the future market. Despite the increasing number of consumers risking the quality of OFD services, more research is needed as to what factors may contribute to a higher level of satisfaction, which is customer delight. This quantitative study sought to identify the primary factors for each service quality dimension contributing to customer delight, the relationship between the service quality dimensions and customer delight, and the implications for service support and recommendations. An adopted survey questionnaire based on the ServQual Model was distributed to social media platforms among Generation. A total of 180 responses were collected using purposive sampling and analyzed using descriptive statistics and inferential statistics, Spearman's Rho Correlation. The results reveal that Assurance has a weak and significant relationship with customer delight. Four of the five service quality dimensions have a moderate and significant relationship with customer delight, namely Tangibility, Reliability, Responsiveness, and Empathy. It implies that all the service quality dimensions are correlated with the Customer Delight of Generation Z OFD users in Tacloban City.